Early and Long-Term Outcomes of Carotid Stenting and Carotid Endarterectomy in Women - Pasqui, Edoardo; de Donato, Gianmarco; Alba, Giuseppe; Brancaccio, Brenda; Panzano, Claudia; Cappelli, Alessandro; Setacci, Carlo; Palasciano, Giancarlo (Frontiers in Surgery, 2021)
BACKGROUND: The role of carotid revascularization in women remains intensely debated because of the lower benefit and higher perioperative risks concerning the male counterpart. Carotid Artery Endarterectomy (CEA) and Stenting (CAS) represent the two most valuable stroke prevention techniques due to large vessel disease. This study investigates the early and late outcomes in female sex in a real-world everyday clinical practice. METHODS: Data were retrospectively analyzed from a single-center database prospectively compiled. A total of 234 procedures, both symptomatic and asymptomatic, were identified (98 CEA and 136 CAS). Perioperative risks of death, cerebral ischemic events, local complications were analyzed and compared between the two groups. Long-term outcomes were evaluated in terms of overall survival, freedom from ipsilateral stroke/TIA, and freedom from restenosis (>50%) and reintervention. RESULTS: Women who underwent CAS and CEA did not differ in terms of perioperative ischemic cerebral events (2.2% vs 0%, p=0.26) and death (0.8% vs 0%, p=1). Other perioperative and 30-day outcomes were similarly distributed within the two groups. Kaplan-Meier curves between CAS and CEA groups highlighted no statistical differences at six years in terms of overall survival (77.4% vs. 77.1%, p=0.47), of ipsilateral stroke/TIA (94.1% vs. 92.9%, p=0.9). Conversely, significant differences were showed in terms of 6 years freedom from restenosis (93.1% vs 83.3%, p=0.03) and reinterventions (97.7% vs 87.8%, p=0.015). CONCLUSION: Our results revealed that both CEA and CAS have acceptable perioperative risk in women. Long-term outcomes highlighted favorable indications for both procedures, especially for CAS, that appeared to be an excellent alternative to CEA in female patients when performed by well-trained operators.